Marketing Research Trends: Issues and Research Direction - Linus Osuagwu (International Journal of Business Studies, 2021)
Marketing research is the systematic and objective conceptualization of a marketing problem, and the consequent collection, analysis, interpretation and reporting of data and information in order to clarify the marketing problem and/or solve it. It has both theoretical and practical forms of importance, with varying trends in issues, methods and practices. This paper examines salient marketing research trend issues and proposes a research direction in business organizations which will help to provide relevant theoretical and practical insights and opportunities.